Characterising the financial cycle: A multivariate and time-varying approach - Yves Stephan Schüler; Paul P. Hiebert; Tuomas A. Peltonen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We extract and analyse financial cycles for 13 European Union countries using a quarterly dataset spanning over 1971-2013. For identification of financial cycles, we employ a novel spectral approach determining the most important common cyclical fluctuations across total credit, residential property prices, equity prices, and benchmark bond yields. Results suggest that the most important financial cycles are on average 12 years, but with some dispersion across countries. Compared to business cycles, financial cycles have more important fluctuations in the medium term (8-20 years); but less important fluctuations in the short run (2.5-8 years). Regarding the extracted financial cycles, credit and residential property prices best summarize contemporaneous movements across financial indicators in almost all country cases.
Keywords: E30; E40; C54; 330